Interleukin‐28B genetic variants in untreated Italian HCV‐infected patients: a multicentre study. (17th July 2014) - Mottola, Leonardo; Cenderello, Giovanni; Piazzolla, Valeria A.; Forte, Paolo; Carretta, Vito; Mecenate, Fabrizio; Brancaccio, Giuseppina; Minisini, Rosalba; Zuin, Massimo; Terreni, Natalia; Monti, Monica; Colombo, Alberto Eraldo; et al.
Abstract Background & Aims Different prevalence of favourable IL28BCC genotype have been reported in studies performed in different countries around the world. Data on distribution of IL28B genotypes in healthy Italian subjects are lacking. Methods Studies on prospectively collected untreated chronic HCV‐infected Italian patients led to conflicting results. To investigate the prevalence of IL28B genotypes in untreated HCV‐infected patients and in subjects able to clear HCV, and to compare them to the prevalence registered in healthy Italian controls. To evaluate IL28B prevalence across different HCV genotypes. Results IL28BCC was observed in 30.9% of chronic HCV patients, in 71.0% of subjects able to clear HCV infection and in 41.6% of the Italian controls. The frequency of IL28BCC was higher in HCV genotype 2 and 3 than in 1 (38.3 vs. 28.2) (P = 0.02). Levels of ALT higher in IL28BCC than in non‐CC were observed regardless of HCV genotypes (P = 0.0014). Conclusions IL28BCC frequencies progressively decline from subjects with spontaneous HCV clearance to normal non‐infected subjects and to chronically infected. This study suggests that patients with IL28BCC, if genotype 1, are able to clear HCV more often than if genotype 2 and 3 infected, and that CC genotype is associated with higher grade of necro‐inflammation.